Cognição e conceptualização do tempo: o processo da significação do tempo linguístico de alguns enunciados em língua portuguesa - Iagallo, Patricia Ormastroni [UNESP] (2015)
The Cognitive Semantics, concerned about what happens in the speaker's mind on the meaning process, have two major assumptions: (i) conceptual structure derives from embodiment, (ii) semantic structure reflects conceptual structure. We check these two hypotheses, and our object was the notion of time in Portuguese. First, we described the conceptual structure of TIME by building the conceptual system of time, which uses interdisciplinary studies as physics, biology, psychology and sociology. After this, we found forms in Portuguese that have the notion of the time line and we categorized them in three frames of temporal reference, and we constructed the semantic structure of TIME. We analyzed the conceptual structure and the semantic structure and we can note how important a description of the conceptual structure is. The total description of what we mean by TIME necessarily needs a look at how the language works (deictic property of language), and at other structure of other concepts, forming the metaphorical language of time (conceptual metaphors). Thus, we conclude that the full description of what we mean by TIME necessarily needs a look at the conceptual structure of TIME, and therefore the Theory of Lexical Concepts and Cognitive Models is adequate to describe how the access to our encyclopedic knowledge of time is, and we can prove the efficacy of the two basic assumptions of research in Cognitive Semantics